2015
DOI: 10.1007/s11104-015-2667-2
|View full text |Cite|
|
Sign up to set email alerts
|

Availability of fertiliser sulphate and elemental sulphur to canola in two consecutive crops

Abstract: Aims We compared elemental sulphur (ES) and sulphate fertilisers in terms of yield and S uptake. Methods Two consecutive canola crops were grown on 35 S-labelled soil amended with ammonium sulphate, ES-bentonite pastilles (90 % ES), or S-fortified ammonium phosphate (NP) fertilisers containing both sulphate-S and ES (5-8 % ES). The shoot yield, S concentration and specific activity of S in the shoot were determined. Results In the first crop, the yield was significantly lower in the control (without added ES) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…The estimated oxidation rate was around 0.005 d −1 , which is in good agreement with the value estimated from a pot trial with MES fertilizer (0.007 d −1 ; Degryse et al, 2016). Based on the oxidation rates found in this study and given the temperature dependence of ES oxidation, around 40% is expected to be oxidized during 1 yr at mid-temperate latitudes assuming that the soil has a similar oxidation capacity as the ones used in this study.…”
Section: Oxidation Rate Of Elemental Sulfur Particles Vs Granular Fesupporting
confidence: 87%
See 1 more Smart Citation
“…The estimated oxidation rate was around 0.005 d −1 , which is in good agreement with the value estimated from a pot trial with MES fertilizer (0.007 d −1 ; Degryse et al, 2016). Based on the oxidation rates found in this study and given the temperature dependence of ES oxidation, around 40% is expected to be oxidized during 1 yr at mid-temperate latitudes assuming that the soil has a similar oxidation capacity as the ones used in this study.…”
Section: Oxidation Rate Of Elemental Sulfur Particles Vs Granular Fesupporting
confidence: 87%
“…They also found that, while micronized ES was as effective as SO 4 -S fertilizer, responses to the ES-bentonite fertilizer were minimal in the first year and still limited in the second year (average oxidation estimated to be 14%) despite thorough mixing of the soil before the second-year experiment. In a recent pot trial study using inverse isotope dilution, we found negligible contribution of ES pastilles to S uptake by canola in two consecutive crops (Degryse et al, 2016). Some other studies found better performance of ES-bentonite products in the second or subsequent years after initial application Solberg et al, 2007).…”
Section: Oxidation Rate Of Elemental Sulfur Particles Vs Granular Fementioning
confidence: 56%
“…Another example showing the importance of using multiple S rates to compare various S sources is demonstrated in a recently published study by Degryse et al (2016) for two successive canola crops (6 wk each) on comparing AS with two MAP-(ES+AS) products as shown in Table 3. Both MAP-(AS+ES) products were statistically as effective as AS in dry matter yield based on a single rate at 20 mg total S kg -1 for the first canola crop.…”
Section: Greenhouse Experimentsmentioning
confidence: 95%
“…Table 3. Dry matter yield (DMY) and S uptake by two successive canola crops (6 wk each) obtained with ammonium sulfate (AS) and two granular monoammonium phosphate (MAP)-(AS+ elemental sulfur [ES]) products (Degryse et al, 2016). and resulted in enhancing S uptake by the second crop.…”
Section: Greenhouse Experimentsmentioning
confidence: 99%
See 1 more Smart Citation